Function of the Infrapatellar Fat Pad and Advanced Hoffa's Disease With Ossification - Murat KARKUCAK,; Erhan ÇAPKIN,; İpek CAN,; Avni Mustafa ÖNDER,; Ali KÜPELİ3, (Archives of Rheumatology, 2014)
Being one of the conditions presenting with patellar pain, Hoffa's syndrome is characterized with inflammation of the fat tissue in the patellar region. In advanced stage, this may lead to transformation of the fibrocartilage tissue and ossification of the infrapatellar fat pad. Some cases can be associated with tumors or tumor-like conditions. In this article, we describe a 72-year-old female case suffering from knee pain for a long time and discuss the end-stage Hoffa's disease and function of the infrapatellar fat pad in the light of literature.